Expression of Protein SOX9 in Biliary Atresia. Issue 2 (16th February 2022) - Arboleda-Bustan, Jenny E.; Ribalta, Teresa; Albert, Asteria; Cuadras, Daniel; Martín-Solé, Oriol
ABSTRACT: Objectives: Biliary atresia (BA) is still an enigmatic disease. Deeper knowledge of its pathophysiology could help develop better treatments. SOX9 regulates bile duct development, liver regeneration and fibrosis; therefore, it could be determinant in characterizing BA liver damage. Aim: To study if there is a SOX9 expression pattern in liver biopsies from BA patients. Methods: Liver biopsies from BA patients (group BA), from age-matched infants without primary hepatic disease (group Control), and from patients with other liver conditions (group OLC) were compared. Expression of SOX9 was checked for: amount, intensity of immunoreaction, localization within ductular structures, perifibrotic epithelial cells, and lobular cells. The scores were added to create a scale from 0 to 11 that allowed group comparison. SOX9 Scale and liver survival were also looked for a correlation. Results: All BA cases had a score >4, while all controls scored <4. OLC livers scored 1 to 8 (3.5 ± 2.0) ( P  < 0.001 between all groups). A cut-off at 4 had 100% sensitivity and 88.24% specificity to differentiate BA from Controls and from OLC (area under receiver operating characteristic curve: 0.9989 (95% confidence interval: 0.9964–1.000). Strong expression of SOX9 was observed mainly in the nuclei of proliferated ductules of portal spaces and fibrotic bridges. SOX9 Scale score could not be related to liver survival in this study. Conclusion: In BA livers, SOX9 is mainly expressed in reactive ductular epithelium, following a pattern significantly different from that seen in non-BA patients; thus, SOX9 Scale may have a role in the diagnosis of BA.